Supply chain management - Stanton, Daniel (--For dummies., 2021)
Supply Chain Management For Dummies, 2nd Edition guides you to an understanding of what a supply chain is and how to leverage this system effectively across your business, no matter its size or industry. This book helps you learn about the areas of business that make up a supply chain, from procurement to operations to distribution. And it explains the importance of supporting functions like sales, information technology, and human resources. You'll be prepared to align the parts of this system to meet the needs of customers, suppliers, and shareholders. By viewing the company as a supply chain, you'll be able to make decisions based on how they will affect every part of the chain. To help you fully understand supply chains, the author focuses on the Supply Chain Operations Reference (SCOR) model. This approach allows all types of professionals to handle their work demands. - Use metrics to improve processes - Evaluate business risks through analytics - Choose the right software and automation processes - Plan for your supply chain management certification and continuing education.